ANALISIS PREFERENSI SISWA MELANJUTKAN KE SMA NEGERI 4 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU TAHUN PELAJARAN 2014/2015 - Asyari, Abu Asyari Abu; Umari, Tri Umari Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This watchfulness aims: 1) to analyze internal factors that be preference student chooses continue to senior high school. 2) to analyze external factors that be preference student chooses continuing to senior high school. 3) to detect category preference student internal chooses to senior high school. 4) to detect category preference student external chooses to senior high school. this watchfulness is carried out at senior high school iv district marpoyan jln adi sucipto. as to this watchfulness time in october 2014 until december 2014. this watchfulness belongs descriptive watchfulness that aims to describe systematically factual and accurate hit fact and certain population characters that are population in these watchfulness SMAN 4 Pekanbaru in tenth year that consists of 10 class that number 325 person students teachings year 2014/2015. In this watchfulness, researcher takes 50% from population total. for that, this watchfulness sample is taken student in class x1, x2, x4,  and x7 that number 144. based on watchfulness analysis result that done so can be taken conclusion: 1) preferensi student from internal factor has chosen to continue to senior high school partly big because finished senior high school has wanted to continue to college, want to get proper job, value enough subsidize, as according to aim,  and a minority minor part a minor part because want to finish study to s3. 2) preferensi student from external factor chooses to continue to senior high school partly big because on approval parents, deepen science has general, base the science has been studied at junior high school, achievable school cost by parents economy ability. 3) internal factor category that be preferensi student in choose to continue to senior high school a large part present in tall category. 4) while in external factor category that be preferensi student chooses to continue to senior high school absolut majority present in category. Keywords: Tentations